Beliefs About Self-Compassion: Implications for Coping and Self-Improvement. (September 2021) - Chwyl, Christina; Chen, Patricia; Zaki, Jamil
Self-compassion—treating oneself with care and understanding during difficult times—promotes adaptive coping and self-improvement. Nonetheless, many people are not self-compassionate. We examined a key barrier people face to treating themselves self-compassionately: their negative beliefs about self-compassion (i.e., that it leads to complacency, indulgence, or irresponsibility). Across three studies, the more people held these negative beliefs, the less self-compassionately they reported responding to a real-world event (Study 2) and hypothetical emotional challenges (Studies 1 and 3). Self-compassionate responding, in turn, predicted adaptive coping strategies and intentions for self-improvement. Experimentally inducing people to hold positive, as opposed to negative, beliefs about self-compassion predicted self-compassionate responding 5 to 7 days later (Study 3). By recognizing and targeting peoples' beliefs, our findings highlight the importance of reducing such beliefs that are barriers to practicing self-compassion, as a means to improve the way people respond to difficult times.